A GLP‐1/glucagon (GCG)/CCK2 receptors tri‐agonist provides new therapy for obesity and diabetes. (20th May 2022) - Zhao, Songfeng; Yan, Zhiming; Du, Yue; Li, Zeyun; Tang, Chunli; Jing, Lin; Sun, Lidan; Yang, Qimeng; Tang, Xueling; Yuan, Yongliang; Han, Jing; Jiang, Neng
Abstract : Background and Purpose: Glucagon‐like peptide‐1 (GLP‐1) and glucagon (GCG) receptor dual agonist have promising therapeutic effects in the treatment of obesity and diabetes. Moreover, GLP‐1 and cholecystokinin 2 (CCK2 ) dual agonists have been shown to restore pancreas function and improve glycaemic control in preclinical studies. We describe, for the first time, the beneficial effects of GLP‐1/glucagon receptor and GLP‐1/CCK2 dual agonists, which can be integrated into one peptide, resulting in significant anti‐diabetes and anti‐obesity effectiveness. Experimental Approach: The in vitro potency of this novel peptide Xenopus (x) GLP‐1/GCG/CCK2 tri‐agonist ( x GLP/GCG/gastrin) against GLP‐1, GCG, CCK1 and CCK2 receptors was determined on cells expressing the corresponding receptors by cAMP accumulation or ERK1/2 phosphorylation assays. The in vivo anti‐diabetes and anti‐obesity effects of this tri‐agonist xGLP/GCG/gastrin were studied in both db/db and diet induced obesity (DIO) mice. Key Results: xGLP/GCG/gastrin was a potent and selective GLP‐1, GCG and CCK2 tri‐agonist. In DIO mice, the metabolic benefits of xGLP‐1/GCG/gastrin, such as reduction of body weight and hepatic lipid contents were significantly better than those of the peptide ZP3022 (GLP‐1/CCK‐2 dual agonist) and liraglutide. In a short‐term study in db/db mice, xGLP/GCG/gastrin treatment had considerable effects, increasing islet numbers, islet areas and insulin content. In a long‐term treatment study using db/db mice, xGLP‐1/GCG/gastrin showed a significantly and sustained improvement in glucose tolerance and glucose control compared with that of liraglutide, ZP3022, cotadutide (GLP‐1/GCG dual agonist) and xGLP/GCG‐15. Conclusions and Implications: These results demonstrate the therapeutic potential of xGLP‐1/GCG/gastrin for the treatment of obesity and diabetes.